Densidades de plantas de Urochloa decumbens em convivência com Corymbia citriodora - Rocha Pereira, Maria Renata [UNESP]; Ferreira Souza, Guilherme Sasso; Cardoso Silva, Jose Iran; Matins, Dagoberto [UNESP] (Universidade Estadual de Londrina (UEL), 2011)
This study aimed to evaluate the effects of plant densities of Urochloa decumbens on the early growth of Corymbia citriodora. The experimental design was completely randomized design with four replications, each plot consisted of a of 60 L capacity vase. The signal grass densities were 0, 20, 40, 80 and 160 plants m(-2), along with one eucalyptus plant. At the end of eight months of living together increase in height and in diameter and plant dry mass of eucalyptus and signal grass were carried out. The eucalyptus characteristics were influenced by all the weed populations, the effect being more pronounced with the increasing of grass density.
Plant densities of Urochloa decumbens in coexistence with Corymbia citriodora
Keywords: Brachiaria; eucalyptus; weed competition; weed interference